General Summability Methods in the Approximation by Bernstein–Chlodovsky Operators. (4th June 2021) - Alemdar, Meryem Ece; Duman, Oktay
Abstract: In this paper, by using regular summability methods we modify the Bernstein–Chlodovsky operators in order get more general and powerful results than the classical aspects. We study Korovkin-type approximation theory on weighted spaces. As a special case, it is possible to Cesàro approximate (arithmetic mean convergence) to the test function e 2 ( x ) = x 2 although it fails for the classical Bernstein–Chlodovsky operators. At the end of the paper, we extend our results to the multi-dimensional case.